A therapy-grade protocol for differentiation of pluripotent stem cells into mesenchymal stem cells using platelet lysate as supplement - Luzzani, Carlos Daniel (2015)
Introduction: Mesenchymal stem cells (MSCs) are a promising source of cells for regenerative therapies. Although they can be isolated easily from several tissues, cell expansion is limited since their properties are lost with successive passages. Hence, pluripotent derived MSCs (PD-MSCs) arise as a suitable alternative for MSC production. Nevertheless, at present, PD-MSC derivation protocols are either expensive or not suitable for clinical purposes. Methods: In this work we present a therapy-grade, inexpensive and simple protocol to derive MSCs from pluripotent stem cells (PSCs) based on the use of platelet lysate (PL) as medium supplement. Results: We showed that the PD-MSCPL expressed multiple MSC markers, including CD90, CD73, CD105, CD166, and CD271, among others. These cells also show multilineage differentiation ability and immunomodulatory effects on pre-stimulated lymphocytes. Thorough characterization of these cells showed that a PD-MSCPL resembles an umbilical cord (UC) MSC and differs from a PSC in surface marker and extracellular matrix proteins and integrin expression. Moreover, the OCT-4 promoter is re-methylated with mesenchymal differentiation comparable with the methylation levels of UC-MSCs and fibroblasts. Lastly, the use of PL-supplemented medium generates significantly more MSCs than the use of fetal bovine serum. Conclusions: This protocol can be used to generate a large amount of PD-MSCs with low cost and is compatible with clinical therapies.